Examining the Aftereffects of Hurricane Katrina in New Orleans: A Qualitative Study of Faculty and Staff Perceptions. (2nd May 2012) - Burnham, Joy J.; Hooper, Lisa M.
Abstract : Researchers have reported how Hurricane Katrina has affected teachers who work with Kindergarten to Grade 12 (K-12), yet little is known about how the natural disaster has affected other important K-12 faculty and staff (e.g., coaches, librarians, school counselors, and cafeteria workers). Missing from the literature is the impact that this natural disaster has had on these formal (school counselors) and informal (coaches, librarians) helpers of K-12 students. Using a focus group methodology, the authors examined the aftereffects of Hurricane Katrina on 12 school employees in New Orleans, Louisiana, 18 months after the hurricane. Informed by qualitative content analysis, three emergent themes were identified: emotion-focused aftereffects, positive coping, and worry and fear. The implications for future research and promoting hope in mental health counseling are discussed.